FUNKCJA FISKALNA PODATKÓW W POLSCE W LATACH DZIEWIĘĆDZIESIĄTYCH - Kurowski, Wojciech (Wydział Prawa i Administracji UAM, 1998)
The system transformation in Poland had the effect of changing the structure of the State income towards increasing the importance o f taxes what was a result of limiting State property in the national economy as well as of abandoning central regulation of prices and salaries. But independently on change in property matters and, consequently, on the increased importance of instruments of income collecting within market economy - the “philosophy” of taxes itself is also changing. The point is that the aims of taxes are shifting and - first of all - their hierarchy. If within the framework of centrally planned economy the fiscal function of taxes was a problem of secondary importance - it becomes of fundamental importance within market economy. This difference does involve essential consequences for the shape of taxes system and particular types of taxes. The present elaboration relates to the decade of 90-ties and is an attempt to evaluate realisation o f the task of taxes - namely, to assure relatively high income level for the State budget. This task is just expressed in fiscal function of taxes. The object of considerations is the structure of fiscal income in the State budget in Poland. An attempt to analyse charge for the population resulting from income tax for individuals was also undertaken. Because of the limited size of the article only charges for the income of the population with income tax for individuals as paid in accordance with general rules were submitted to the analysis. So the article does not treat problems of charges resulting from paying such a tax in form of a global sum. The stress laid on tax charges for the population results from the fact that this problem is the most perceptible and becomes therefore an object of heated debates by specialist and among ordinary tax-payers. In final part of the paper some respective international comparisons have been made and the attention was drawn to the problem of the amount of costs for collection of taxes in Poland.
FISCAL FUNCTION OF TAXES IN POLAND DURING NINETIES